Relationship between initial and time-dependent cracks in charge transport of solution-processed organic thin-film transistor. (13th August 2017) - Jung, Ji-Hoon; Kim, Young-Rae; Choe, Eunji; Song, Dong-Seok; Bae, Jin-Hyuk
ABSTRACT: We report on the comprehensive effect of initial and time-dependent crack on the charge transport of 6, 13-bis (triisopropylsilyethynyl) pentacene (TIPS-PEN) thin-film transistors (TFTs) upon exposure to air. Among the two types of TIPS-PEN films, with and without initial thermal cracks, temporally generated cracks were found to be severely affected by the initial status of the thermal cracks upon air-exposure. After 12 months of air-exposure, the charge transport characteristics of TIPS-PEN TFTs with initial thermal cracks degraded up to 98%, while those without initial thermal cracks degraded only 88%. Based on our long-term experimental results, we conclude that the initial physical status of the cracks play a significant role in the growth of time-dependent cracks and the capability of charge transport in solution-processed TFTs.